(untitled) (Research, Society and Development, 2022)
Objectives: To analyze the consequences of falls on the quality of life of the elderly in the home environment. Methodology: The methodology of this work consists, essentially, of research with a broad bibliographic review. The construction procedures of these studies will be based on information taken from scientific articles published in the last 10 years and researched in the Ministry of Health, in the Latin American and Caribbean Literature databases Health Sciences (LILACS), electronic page of the Virtual Health Library (BIREME) and Scientific Electronic Library Online (SciELO). Results and discussion: Falls can have serious physical and psychological consequences, including injuries, hospitalizations, mobility disturbance, fear of falling again, activity restriction, functional decline, institutionalization and even death. Conclusion: Falls in the elderly are multifactorial events, and knowledge of their risk factors is important to guide the planning of preventive measures.